Algebra - cube roots and square roots

Algebra Level 1

y = x + x 2 + 1 3 + x x 2 + 1 3 \large y=\sqrt[3]{x+\sqrt{x^2+1}}+\sqrt[3]{x-\sqrt{x^2+1}}

Given the above equation, find x x in terms of y y .

x = ( y 2 + 2 ) 2 x=\dfrac{(y^{-2}+2)}{2} x = ( y 2 + 3 ) 2 x=\dfrac{(y^2+3)}{2} x = y ( y 2 + 3 ) 2 x=\dfrac{y(y^2+3)}{2} x = y ( y 2 + 2 ) 2 x=\dfrac{y(y^2+2)}{2}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Sep 16, 2018

y = x + x 2 + 1 3 + x x 2 + 1 3 Cubing both sides. y 3 = x + x 2 + 1 + 3 ( x + x 2 + 1 3 ) 2 x x 2 + 1 3 + 3 x + x 2 + 1 3 ( x x 2 + 1 3 ) 2 + x x 2 + 1 = 2 x + 3 ( x + x 2 + 1 ) ( x x 2 + 1 ) 3 ( x + x 2 + 1 3 + x x 2 + 1 3 ) = 2 x + 3 1 3 y = 2 x 3 y \begin{aligned} y & = \sqrt[3]{x+\sqrt{x^2+1}} + \sqrt[3]{x-\sqrt{x^2+1}} & \small \color{#3D99F6} \text{Cubing both sides.} \\ y^3 & = x+\sqrt{x^2+1} + 3\left(\sqrt[3]{x+\sqrt{x^2+1}}\right)^2 \sqrt[3]{x-\sqrt{x^2+1}} + 3\sqrt[3]{x+\sqrt{x^2+1}}\left(\sqrt[3]{x-\sqrt{x^2+1}}\right)^2 + x-\sqrt{x^2+1} \\ & = 2x + 3\sqrt[3]{(x+\sqrt{x^2+1})(x-\sqrt{x^2+1})} \left(\color{#3D99F6}\sqrt[3]{x+\sqrt{x^2+1}} + \sqrt[3]{x-\sqrt{x^2+1}}\right) \\ & = 2x + 3\sqrt[3]{-1}\color{#3D99F6} y \\ & = 2x - 3y \end{aligned}

x = y 3 + 3 y 2 = y ( y 2 + 3 ) 2 \implies x = \dfrac {y^3+3y}2 = \boxed{\dfrac {y(y^2+3)}2}

Naren Bhandari
Sep 21, 2018

Let A = x 2 + 1 A 2 = x 2 + 1 A=\sqrt {x^2+1}\Rightarrow A ^2=x^2+ 1 ,also we have that ( a + b ) 3 = a 3 + b 3 + 3 a b ( a + b ) (a+b)^3 = a^3+b^3+3ab(a+b) then our expression becomes y = x + A 3 + x A 3 y 3 = 2 x + 3 ( x + A ) ( x A ) 3 ( x + A 3 + x A 3 ) y 3 = 2 x + 3 y x 2 A 2 3 \begin{aligned} y & ={\color{#20A900} \sqrt[3]{x+A } + \sqrt[3]{x-A}}\\ y^3 & =2x +3\sqrt[3]{(x+A)(x-A)}\left({\color{#20A900}\sqrt [3]{x+A} + \sqrt[3]{x-A}}\right) \\ y^3& = 2x +3y \sqrt[3]{x^2-A^2}\end{aligned} Undo the substitution of A 2 A^2 and simplying we have y 3 = 2 x 3 y x = y ( y 2 + 3 ) 2 y^3 = 2x- 3y \implies x=\dfrac{y(y^2+3)}{2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...